Correlation of lanthanum dosage with lanthanum deposition in the gastroduodenal mucosa of dialysis patients. Issue 9 (11th August 2017) - Hattori, Kimiaki; Maeda, Tamaki; Nishida, Shinya; Imanishi, Miyuki; Sakaguchi, Masahiro; Amari, Yoshifumi; Moriya, Takuya; Hirose, Yoshinobu
Abstract : Lanthanum (La) deposition has been observed in gastrointestinal mucosa of dialysis patients treated with La carbonate to treat hyperphosphatemia in the 6 years since its authorization in Japan. We investigated gastrointestinal biopsies from 112 dialysis patients, and found 15 cases of histiocytic aggregation with crystalloids and one case of duodenitis with histiocyte aggregation without crystalloids in the 30 patients treated with La carbonate. No histiocytic lesions were observed in the 82 patients without La carbonate administration. So far in total 70 cases of La deposition in the alimentary tract have been reported, including our 16 cases. Neither clinical nor histological findings other than histiocytic aggregation were specific in the patients with La deposition. We also compared the groups with and without La deposition, revealing that the daily and total doses of La carbonate showed statistically significant correlations with La deposition. However the causality with their histologic features, e.g. intestinal metaplasia and degree of inflammation, were inconclusive between the two groups. Although no critical symptoms have been reported, it is necessary to accumulate more cases to clarify the mechanism of La deposition, because dialysis patients must take phosphate buffers for a long period.